Efektivitas video animasi dalam edukasi oral hygiene terhadap pengetahuan pencegahan karies gigi pada anak kelas II - Herlinda Dwiyanti; Sri Hartati; Ryka Juaeriah; Sri Maryati (JOURNAL OF Community Health Issues, 2026)
Background: Dental caries is one of the most common oral health problems among school-aged children. Inadequate knowledge of oral hygiene and dental caries prevention may contribute to the high prevalence of dental caries in children. Health education using animated video media is an engaging approach that is appropriate for children's developmental stage and may help improve their knowledge of dental caries prevention. Purpose: To determine the effect of oral hygiene education using animated video media on knowledge of dental caries prevention among Grade II students at MI Roudotutta’lim Batujajar, West Bandung Regency. Method: This quantitative study employed a pre-experimental design with a One-Group Pretest–Posttest Design. The study population consisted of 103 Grade II students, who were selected using total sampling. Data were collected using a knowledge questionnaire administered before and after the intervention. Data were analyzed using univariate analysis and the Marginal Homogeneity Test. Results: Before the intervention, 40 participants (38.8%) had low knowledge. Following oral hygiene education using animated video media, 86 participants (83.5%) demonstrated high knowledge. The results of the Marginal Homogeneity Test showed a p-value of 0.000 (p < 0.05), indicating a statistically significant difference in knowledge before and after the intervention. Conclusion: Oral hygiene education using animated video media had a significant effect on students' knowledge of dental caries prevention. Animated video media can be recommended as an engaging educational medium for promoting oral health and preventing dental caries among elementary school children.